Proceedings Electronic Components and Technology, 2005. ECTC '05.
DOI: 10.1109/ectc.2005.1441302
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between liquid Sn-Bi based solders and contact metals for high temperature applications

Abstract: • This is a conference paper [ c IEEE]. It is also available at:http://ieeexplore.ieee.org/ Personal use of this material is permitted.However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution to servers or lists, or to reuse any copyrighted component of this work in other works must be obtained from the IEEE AbstractLiquid solder interconnects are promising as an alternative approach to conventional high me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, due to their high surface energy, nanoparticles increase the probability of agglomeration with each other in the solder matrix. Such nonuniform dispersion and aggregation of nanoparticles degrades the reliability of the solder matrix [123][124][125][126], an optimal content evaluation for each nanoparticle should be made. Strengthening the effect by adding nanoparticles can be obtained by the following factors.…”
Section: Mechanical Property Of Sn-bi Soldermentioning
confidence: 99%
“…However, due to their high surface energy, nanoparticles increase the probability of agglomeration with each other in the solder matrix. Such nonuniform dispersion and aggregation of nanoparticles degrades the reliability of the solder matrix [123][124][125][126], an optimal content evaluation for each nanoparticle should be made. Strengthening the effect by adding nanoparticles can be obtained by the following factors.…”
Section: Mechanical Property Of Sn-bi Soldermentioning
confidence: 99%
“…Li et al [29] have done research on the effect of a small amount of Al addition on the wettability of the Sn-58Bi solder. Due to Al being too active or the flux being not matched to this solder, it was found that the wettability of the Sn-58Bi solder became poorer after adding 2 wt.% Al to the eutectic Sn-58Bi solder.…”
Section: Wettabilitymentioning
confidence: 99%
“…The IMC nucleation, growth, and its type are responsible for the solder reliability [83,84]. In addition, the IMC formed at first could function as a hard diffusion barrier to restrain further IMC growth [29]. At the same time, a part of Bi atoms dissolve into the Cu 6 Sn 5 intermetallic compound layer and then segregate at the Cu/Cu 3 Sn interface.…”
Section: Intermetallic Compounds Layermentioning
confidence: 99%
See 1 more Smart Citation
“…One way to slow down the liquid state interfacial reaction is by adding a special inhibitor additive into the solder alloy. However, it has been found that amongst a broad range of additional elements studied, some limited success has only been achieved with the addition of copper to the eutectic Sn-Bi solder [2], which is the most suitable low melting solder for liquid solder applications. Al has also been reported as a suitable inhibitor [1], but has only been tested successfully under vacuum conditions, and interferes with solder wetting in air.…”
Section: Introductionmentioning
confidence: 99%